The effect of quality of service experience on consumers' loyalty to music streaming services: Time pressure as a moderator - Zhang, Yizhou; Zhang, Mengze (Frontiers in Psychology, 2022)
This study investigates how the quality of service experience (QSE) impacts users' satisfaction and loyalty to music streaming services. To this end, the sense of insufficient time to do things, a moderated mediation model, is adopted to examine the mediating role of satisfaction and the moderating role of time pressure from working. By using structural equation modeling, the results reveal that QSE is positively related to users' satisfaction and loyalty to music streaming services. The results also show that the QSE positively influences users' loyalty through satisfaction. Furthermore, time pressure, acting as a moderator, positively affects the relationship between QSE and satisfaction and the relationship between satisfaction and loyalty.